Separating the wheat from the chaff - a taxonomy of open innovation - Duarte, Vanessa (2012)
Purpose – The main objective of this paper is to shed light on the confusion of terminologies related to open innovation through the development of an open innovation taxonomy. By analyzing published case studies using numerical taxonomy methods, it proposes a taxonomic classification of open innovation. Design/methodology/approach – Earlier work on firm collaboration and concepts related to open innovation in order to understand the main motivations, and conditions behind open innovation-like strategies is first to be reviewed in this paper. It then proceeds to collect and systematically analyze 20 published case studies, and using numerical taxonomy methods it produces a taxonomic classification of open innovation. As a first approach to taxonomy on open innovation strategies, the UPGMA methodology used seems very promising. The taxonomy of open innovation developed here can also be used as a decision-making tool through the comparison of open innovation strategies inherent in the taxonomy. Findings – Through the numerical taxonomy analysis the paper has been able to objectively create groups of similar cases, and strategies therein. This paper is able to draw some interesting conclusions by identifying two general strategies of collaboration - a free revealing “democratic” strategy and a formal collaboration strategy. The first involves a proliferation of partners whose technical and creative skills are specific to the industry and the source of knowledge, and where the degree of interaction plays an important role. The second broad strategy of cooperation is linked to more formal collaboration, generally firm-firm collaboration; in this group a large focus on markets features, especially technological intensity, was found. Originality/value – This paper adds objectivity to the research of different open innovation strategies by using a method developed in the natural sciences. Based on a systematic review of literature, the paper was able to identify key characters describing features and come up with a taxonomy of open innovation, which goes a significant way towards making sense of the plethora of terminology related to open innovation. Key features of different open innovation strategies are also revealed.